Cholesterol Binds in a Reversed Orientation to TCRβ-TM in Which Its OH Group is Localized to the Center of the Lipid Bilayer. Issue 24 (3rd December 2021) - Wu, Hongyi; Cao, Ruiyu; Wei, Shukun; Pathan-Chhatbar, Salma; Wen, Maorong; Wu, Bin; Schamel, Wolfgang W.; Wang, Shuqing; OuYang, Bo
Graphical abstract: Highlights: NMR characterization of TCRβ-TM in lipid membranes. Identification of a CARC-like motif that binds to cholesterol in TCRβ-TM. The NMR and energetic differences between competitive cholesterol vs. cholesterol sulfate. The enhancement for understanding the molecular basis of T-cell mediated response. Abstract: T cell receptor (TCR) signaling in response to antigen recognition is essential for the adaptive immune response. Cholesterol keeps TCRs in the resting conformation and mediates TCR clustering by directly binding to the transmembrane domain of the TCRβ subunit (TCRβ-TM), while cholesterol sulfate (CS) displaces cholesterol from TCRβ. However, the atomic interaction of cholesterol or CS with TCRβ remains elusive. Here, we determined the cholesterol and CS binding site of TCRβ-TM in phospholipid bilayers using solution nuclear magnetic resonance (NMR) spectroscopy and molecular dynamics (MD) simulation. Cholesterol binds to the transmembrane residues within a CARC-like cholesterol recognition motif. Surprisingly, the polar OH group of cholesterol is placed in the hydrophobic center of the lipid bilayer stabilized by its polar interaction with K154 of TCRβ-TM. An aromatic interaction with Y158 and hydrophobic interactions with V160 and L161 stabilize this reverse orientation. CS binds to the same site, explaining how it competes with cholesterol. Site-directed mutagenesis of the CARC-like motif disrupted the cholesterol/CS binding to TCRβ-TM, validating the NMR and MD results.